Proposals Ninth Five Year Plan 1997-2002 and Annual Plan 1997-1998 - Planning Commission (Planning Commission, 1997)
The National Minorities Development & Finance Corporation was set up in Sept., 94 under Section 25 of the Indian Companies Act 1956. The authorised share capital of this Corporation is Rs.500 crores out of which Central Govt.'s contribution is Rs.125 crores. The rest of the Contribution comes from States/UTs, institutions and individuals interested in the welfare of minorities. The basic objective of the Corporation is to provide assistance to the economic and developmental activities of the minorities with special preference to occupational groups and women. The Corporation extends loans to minorities at concessional rates to the extent of 85% of the project cost subject to a maximum of Rs.85,000/-. The rest of the portion is met by State Govt., financial institutions, beneficiaries etc. The Corporation implements its scheme through the State channelising Agencies.
Minorities and Other Backward Classes Welfare